Dukungan Suami, Orang Tua, dan Mertua dalam Pemberian ASI Ekslusif di Kota Tasikmalaya - Ima Karimah; Irma Nuraeni; Andi Eka Yunianto; Usdeka Muliani (HB PRESS, 2022)
Low breastfeeding is a problem that must be faced together because it can affect children's lives in the future. The lack of exclusive breastfeeding can interfere with child growth and development. Based on several studies in Indonesia, one of the factors that influence the low rate of exclusive breastfeeding is the lack of family support. Exclusive breastfeeding in West Java province in 2018 reached 57.97%. This number is still below the national target (65.16%). Based on the information from the Tasikmalaya City Health Office, the coverage of exclusive breastfeeding in Tasikmalaya City in 2018 reached 69.00%, but has not reached the target. The purpose of this study was to determine the support of husbands, parents, and in-laws in exclusive breastfeeding. This study used a qualitative method of focus group discussions (FGD). This method presented a direct relationship between the researcher and the person providing the information, making it possible to gain insight into the attitudes, motivations and behavior of the target towards the support and barriers to exclusive breastfeeding. There were four informants in this study. The results of this study indicated that the factors that support the success of exclusive breastfeeding in this study were the wishes of the baby's own mother, support from her husband, the baby's grandmother, and health workers who assisted in childbirth.